2015
DOI: 10.2174/1573403x1103150514151750
|View full text |Cite
|
Sign up to set email alerts
|

Minimally-invasive LVAD Implantation: State of the Art

Abstract: Nowadays, the worldwide number of left ventricular assist devices (LVADs) being implanted per year is higher than the number of cardiac transplantations. The rapid developments in the field of mechanical support are characterized by continuous miniaturization and enhanced performance of the pumps, providing increased device durability and a prolonged survival of the patients. The miniaturization process enabled minimally-invasive implantation methods, which are associated with generally benefitting the overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 47 publications
(77 reference statements)
0
58
0
1
Order By: Relevance
“…Minimally invasive VAD implantation methods will hopefully further benefit the overall outcome of patients, but structured investigation of these techniques is needed. Although minimally invasive techniques avoid the need for open sternotomy, they also have a greater potential for malposition, the same cumulative incisional length, and still require an open sternotomy if the right ventricle fails . New technological breakthroughs are expected in the future (e.g.…”
Section: Management Strategies For Patients With Advanced Heart Failurementioning
confidence: 99%
“…Minimally invasive VAD implantation methods will hopefully further benefit the overall outcome of patients, but structured investigation of these techniques is needed. Although minimally invasive techniques avoid the need for open sternotomy, they also have a greater potential for malposition, the same cumulative incisional length, and still require an open sternotomy if the right ventricle fails . New technological breakthroughs are expected in the future (e.g.…”
Section: Management Strategies For Patients With Advanced Heart Failurementioning
confidence: 99%
“…The predetermined point of these effects in LVAD patients is the entry of the inflow cannula into the myocardium and the angle between physiological blood flow and the inflow cannula. Despite the many improvements over the last decades, thrombus formation is still one of the Achilles' heels of LVAD therapy (6)(7)(8). The CE mark study of the HM3 showed no thrombus formation in the first follow ups of the study cohort but longer follow up investigations need to be made in order to fully rule out thrombus formation in the new device (9).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades blood pumps have experienced multiple technical developments such as the creation of artificial pulses or substantial miniaturization and the possibility of minimallyinvasive implantation (4,5). Yet, bleeding complications such as thrombosis are still major disadvantages of LVAD therapy (6)(7)(8).…”
mentioning
confidence: 99%
“…When the LVAD implantation has involved both a left thoracotomy and a limited proximal sternotomy instead of a right thoracotomy for anastomosis of the outflow tract to the ascending aorta (9), it is important to ascertain the position of the distal outflow tract in relation to the sternum as lateral placement of the anastomosis through this approach is more difficult.…”
Section: Caveatsmentioning
confidence: 99%